Combination and comparison of AES and RC4 cryptography in least significant bit (LSB) method in digital image to improve message security - Rahmat Sulaiman (Jurnal Informatika, 2018)
Message security is something that must be kept secretly. However, to maintain the security and the secret of a message it takes two different methods. To maintain the security of messages, the science that has been widely used is to use cryptography. As for maintaining the secret of the message, the science used is steganography. For that, we need a security message that can maintain the security and the secret of the message simultaneously. Various algorithms have been widely applied in data security, but it is unknown which algorithm has a superior speed when applied in the LSB. The test is done by calculating the length of the encryption time process and the decryption time process of each algorithm with the same number of messages and key lengths. Measurement time is done as much as 10 times, then taken average value to get consistent time because system instability. Therefore, we will compare the speed of encryption and decryption process by applying AES and RC4 algorithm to LSB in Visual Studio 2008. In the process of encryption and decryption, the AES algorithm is superior in terms of speed compared to RC4 algorithm. The MSE and PSNR values generated from the encrypted images based on the AES and RC4 algorithm doesn’t show significant value. Overall the AES algorithm is better than RC4 algorithm when applied in LSB.